Rats ejaculate prematurely and increase the sperm output during competitive mating. Issue 4 (3rd July 2020) - Fuentes-Morales, Maria R.; Gutiérrez-Ospina, Gabriel; Fernández-Guasti, Alonso; Cruz, Yolanda; Lucio, Rosa Angélica
Abstract : Rats are gregarious and promiscuous and when a female enters the behavioral estrous, two or more males copulate alternately (mount, intromission or ejaculation are performed by any of them). This circumstance promotes male-male competition that in turns influences the copulatory behavior. Thus, olfactory and visual cues of rivals, in laboratory conditions, shorten the ejaculation latency. Other studies focusing in the presence of a rival found the increment in the sperm number. Until now it is unknown if the simultaneous presence of two males simultaneously influences the copulatory performance and seminal characteristics. Thus, the aim of the present work was to evaluate if sexual competition modifies the copulatory behavior, the sperm number and seminal plug. Sexually experienced Wistar rats were tested in two different copulatory contexts. Non-competitive mating (one male-one female), and competitive mating (two males-one female). The copulatory (mounts, intromissions and ejaculation) and seminal parameters (sperm count and copulatory plug) were analyzed. We found that under competition, there was a shortening of the ejaculation latency due to the reduction in the inter-intromission interval and in the number of intromissions. Respect to the ejaculate, the sperm number increased drastically but the seminal plug maintain its size and weight characteristics. Therefore, sexual competition in male rats affects copulatory behavior and sperm count but not the seminal plug.